Production of Magnesium Silicate from Rice Husk with Variation of NaOH Concentration and Reaction Time Length Using Sol-gel Method - Kalloka, Sultan Hendra Mahardi; Rabbani, Sulthan; Andesra, Zel; Qomariyah, Lailatul (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Rice husk is a by-product of rice production where as much as 9.9 million tons become organic waste. Rice husk ash, which is rich in silica, can be processed into materials that have high selling value. Magnesium silicate is one of the silica-based composite materials with the chemical formula MgSiO3 with an example of its application as a material in the manufacture of magnesium cement. The manufacture of magnesium silicate is done by sol-gel method with NaOH solvent where this method is relatively easy and uses simple equipment. This study was conducted to know the best NaOH concentration and length of reaction time to produce optimal magnesium silicate. The NaOH concentration variables used were 3 M, 5 M, 7 M, and 9 M, while the variable length of reaction time was 90 minutes and 150 minutes. The best NaOH concentration is 7M with 90 minutes of reaction time. This variable gave 49,9% yield of magnesium silicate compared to 3M with 90 minutes reaction time where it gave 17,4% yield. The analytical tests carried out were FITR where this test was carried out to confirm the formation of magnesium silicate